2015
DOI: 10.1016/j.jana.2015.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Provider Perspectives Regarding the Health Care Needs of a Key Population: HIV-infected Prisoners After Incarceration

Abstract: During incarceration, many HIV-infected prisoners receive care and are adherent to medication. However, following release, many have difficulty engaging in HIV care and remaining on antiretroviral therapy (ART). Community-based service providers for HIV-infected releasees have a deep understanding of the health needs and challenges these individuals face on community re-entry. We conducted in-depth qualitative interviews with 38 health care and service professionals in 2 U.S. southern states regarding the barr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 27 publications
2
21
0
3
Order By: Relevance
“…The overarching objective of the intervention was to maintain viral suppression following prison release, and entry into community medical care was presumed to be the critical mediator of this outcome. The intervention was finalized following formative research conducted with prison-based and community service providers as well as former inmates living with HIV infection, as has been previously reported (26, 27). The main elements of the tested intervention included the following:…”
Section: Methodsmentioning
confidence: 99%
“…The overarching objective of the intervention was to maintain viral suppression following prison release, and entry into community medical care was presumed to be the critical mediator of this outcome. The intervention was finalized following formative research conducted with prison-based and community service providers as well as former inmates living with HIV infection, as has been previously reported (26, 27). The main elements of the tested intervention included the following:…”
Section: Methodsmentioning
confidence: 99%
“…There were several individual‐level factors that affected linkage to HIV care following release. Unstable housing or homelessness were the most common barriers to HIV care post‐release . Conversely, Booker et al found that inmates with stable housing 30 days post‐release were over four times more likely to be linked to HIV care .…”
Section: Resultsmentioning
confidence: 99%
“…In addition, several studies identified social support and the presence of children or other dependents as important facilitators to linkage to HIV care among released inmates. Other individual‐level barriers to linkage to HIV care following release included re‐incarceration, HIV‐related stigma, having less than a high school education, and a lack of trust or previous negative experiences with healthcare providers . Conversely, engagement in HIV care and adherence to antiretroviral therapy prior to incarceration, as well as having a dedicated off‐site HIV care provider were all associated with increased linkage to HIV care post‐release.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Exposure to long and short-term imprisonment dramatically increases an individual’s vulnerability towards HIV, STIs, and potentially aggravate the severity of pre-existing (or onset of) drug use, alcohol use, and mental health disorders. 33,34 High levels of HIV/AIDS and alcohol abuse are well-documented among formerly incarcerated populations and have been attributed to issues of re-entry: difficulty re-entering the workforce, adapting to new cultural environments, stigma, and isolation. 35,36 These high levels of risk behaviors among FILM can be attributed to unemployment.…”
Section: Introductionmentioning
confidence: 99%